An octo-aesthetic figuration for learning in times of crisis - Carstens, Delphi (Critical Studies in Teaching and Learning, 2023)
This theoretical paper mobilises a multi-modal figuration – octo-aesthetics – to argue for a transversal approach to HE (higher education) pedagogies appropriate to times of uncertainty. Using the eight independently thinking arms of the octopus as a guide, I deploy eight interrelated conceptual thinking aids to outline the relevance of an ethico-aesthetic paradigm to HE in times of individual, social, and environmental crisis. Deployed as speculative thinking aids, these octo- aesthetic figurations – schizoanalysis, bewilderment, shimmer, ecosophy, ecologicity, holobiont, trans-corporeality, and geontology – reclaim ‘vision’ and ‘objectivity’ from the disembodied all- knowing gaze of ‘Man’ and queer the central, and often unquestioned positions of privilege accorded to this viewpoint in humanist education systems. Calling into question anthropocentric binary/separatist humanist logics and assumptions of objective mastery, octo-aesthetic figurations reveal the onto-ethical outlines of a transversally situated learning modality that defies objectifying majoritarian modes of thinking/learning that are no longer appropriate to pedagogies in times of ecological calamity.